FAKTOR- FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERTUMBUHAN ANAK BALITA DI POSYANDU PAGANG DALAM WILAYAH KERJA PUSKESMAS NANGGALO KOTA PADANG - Nensi, Yepni; Febrina, Febrina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Based on data from the City Health Office fields (DKK) Clinics, the prevalence of disorders of growth has Nanggalo toddlers with an indicator Weight per Age (w/U) is the highest of the toddler weighed 3162, 51 (2,82%) were toddlers under the red line (BGM). The purpose of this research was to determine the factors related to childhood growth in employment within the Pagang Dalam Posyandu working area Puskesmas Nanggalo Padang city 2022. This type of research is survey design with cross sectional analytic study. This research was conducted in February to September 2022. The population in this research is the Moms who have babies at the posyandu Pagang which amounted to 47 people. all populations were sampled. Data collection is done with the interview using kuersioner. The Data processed with the editing, coding, entry and cleaning. Analysis of univariate data with descriptive statistics and data analysis with bivariat chi-square test.The results showed that less than half (36.2 percent) growth in childhood is not normal, more than half (53.2 percent), mother of toddlers have low education, partly (27.7 percent), low intake of toddlers, and less than half (48.9%) of the mother child toddler has socio-economic status is low. There is a meaningful relationship between the mother's education with childhood growth (p value 0.001), There is a meaningful relationship between the intake of toddlers with toddlers (p value 0.001) and there is a meaningful relationship between the socioeconomic status of families with toddlers growth (p value 0.000).Expected through the leadership of the health centers primarily on the officer's service officers KIA, nutrition and other officers in order to improve health services by enabling the return in the granting of PMT every holding of posyandu, conducting public awareness about child growth and nutrition balanced menu toddler on toddlers and child growth evaluation of toddlers at the Posyandu Pagang inside.